Development of Android-Based Learning Application Using Articulate Storyline 3 - Pance Ronaldi Solo; Juliana M.H Nenohai; Ofirenty Elyada Nubatonis (Hipotenusa: Journal of Mathematical Society, 2023)
This research aims to create an Android-based learning application assisted by Articulate Storyline 3 software for class VIII students of SMP Negeri 13 Kupang that is valid, practical, and effective. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection techniques and instruments include interviews, questionnaires, and tests. The data analysis technique uses qualitative and quantitative descriptive analysis techniques. This research produces an Android-based application product named "Relations and Functions" and has met the criteria for validity, practicality, and effectiveness. For media validity, the average assessment by 3 material experts was 4.37, and the average assessment by 3 media experts was 4.38, so it has the "valid" category. For the practicality of the media in small-scale trials, the student response was 4.72, and the effectiveness of the media through the percentage of learning completion was 100%. Meanwhile, in the large-scale trial, the subject teacher's assessment response was 4.5 and the student response was 4.63, so it was in the "practical" category. For media effectiveness, the learning completion percentage was 83.33% and was categorized as "very effective". Thus, the learning application developed is valid, practical, effective, and suitable for use in learning activities.